Validity of Urine Syndecan-1 as A Predictor of Acute Kidney Injury In Pediatric Sepsis Patients - Bambang Pujo Semedi; Arie Utariani; Nugroho Setia Budi; Ninik Asmaningsih; Lucky Andriyanto (Faculty of Medicine-Universitas Airlangga, 2021)
Introduction: AKI (Acute Kidney Injury) complications in sepsis patients generally occur 24 hours after admission to ICU. Creatine Serum Concentration is a standard parameter to diagnose AKI. Unfortunately, the changes in creatine serum concentration will only be seen several days after the decrease of renal function to 50%. The low detection ability has been linked with time loss before preventive therapy is commenced. Furthermore, this instigates the need for biomarkers to ensure early detection. Objective: This study aimed to identify cut-off points of urine syndecan-1 and to measure the prediction ability of urine syndecan-1 towards the AKI occurrence in pediatric sepsis patients. Materials and methods: This study was a prospective cohort study performed at a single center in Dr. Soetomo General Hospital, Surabaya. The inclusion criterion was all children admitted to the resuscitation room from October until December 2019. Furthermore, urine sampling is carried out at 0, 6, 12, and 24 hours for a syndecan-1 urine examination, and every procedure performed on the patient will be recorded. This action was continued up to the third day and aimed to evaluate some factors related to AKI at 48-72 hours of admission. Result and Discussion: Out of 41 pediatric sepsis patients, 30 patients fulfilled the inclusion criteria and 57% had AKI. The value of urine syndecan-1 at hour-0 and hour-6 was significantly featured a cut-off point. Conclusion: The value of urine syndecan-1 at hour-0 and hour-6 are valid parameters to predict the occurrence of AKI grades 1, 2, and 3 in pediatric septic patients at 48-72 hours after their hospital admission. The best cut-off value of urine syndecan-1 at the 0th hour was 0.67 ng/ml.